Children’s Sleep and Human Capital Production - Jagnani, Maulik (The Review of Economics and Statistics, 2024)
Abstract This paper uses exogenous variation in sleep induced by sunset time to present the first human capital estimates of (i) the effects of child sleep from the developing world and (ii) the long-run effects of child sleep in any context. Later sunset reduces children’s sleep: when the sun sets later, children go to bed later but fail to compensate by waking up later. Sleep-deprived children study less and increase nap time and indoor leisure activities. Short-run sleep loss decreases children’s test scores. Chronic sleep deficits translate into fewer years of education and lower primary and middle school completion rates among school-age children.